Diversion Reform in Juvenile Criminal Law Based on Prophetic Restorative Justice - Setiyawan, Deni; Ananda Afit Oktavian; Naufal Andra Maghara Yoga Tama Putra; Muhammad Azimuddin Mohamed (Fakultas Syariah INSURI Ponorogo, 2026)
Restorative justice in the Juvenile Criminal Justice System remains predominantly shaped by pragmatic and secular approaches, limiting its capacity to support substantive character formation among children in conflict with the law. This study examines the integration of prophetic legal values into diversion and rehabilitation processes to strengthen the ethical and transformative dimensions of restorative justice. Using a normative juridical method, the study analyzes the weaknesses of conventional restorative justice practices within the Indonesian juvenile justice framework. The findings indicate that diversion is largely implemented as a formal conflict resolution mechanism through peace agreements, with limited attention to character development and deep value internalization. In response, this study proposes a prophetic restorative justice model grounded in the values of humanization, liberation, and transcendence, offering a more holistic approach to juvenile rehabilitation. The integration of ethical and transcendental dimensions repositions diversion as a structured process of character rehabilitation and sustainable social relationship reconstruction rather than mere case settlement. This study contributes conceptually and normatively by reconstructing restorative justice through a prophetic legal paradigm, while also providing policy-oriented implications for strengthening regulations and technical guidelines to institutionalize prophetic restorative justice within Indonesia's Juvenile Criminal Justice System.